1988
DOI: 10.1073/pnas.85.10.3504
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II allelic variation and susceptibility to pemphigus vulgaris.

Abstract: The autoimmune dermatologic disease pemphigus vulgaris (PV) is associated with the HLA serotypes DR4and DRw6. Susceptibility to PV could be conferred either by sequences shared between the DR4 and DRw6 haplotypes or by different sequences in these haplotypes. We have examined the distribution of DR and DQ fl-chain and DQ a-chain alleles in PV patients and in control subjects by hybridization with oligonucleotide probes and sequence analysis of in vitro ampli- (8). In population studies, PV is strongly associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
52
0
3

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 184 publications
(57 citation statements)
references
References 22 publications
2
52
0
3
Order By: Relevance
“…Thus, the observed distribution of DRBI and DQB alleles among DR4+ PV patients and controls suggested that the Dw10 DRB1 allele was responsible for the observed association with DR4. The Dw1O DRBJ allele differs from the other DRBJ alleles of the DR4 haplotype in the third hypervariable region in containing the "IDE" (Ile-67, Asp-70, and Glu-71) epitope which is, therefore, implicated in the susceptibility of DR4' individuals to PV (10)(11)(12). Although the same IDE epitope is found in the third hypervariable region of the most-common DRw6 DRBI allele, 6A (Fig.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Thus, the observed distribution of DRBI and DQB alleles among DR4+ PV patients and controls suggested that the Dw10 DRB1 allele was responsible for the observed association with DR4. The Dw1O DRBJ allele differs from the other DRBJ alleles of the DR4 haplotype in the third hypervariable region in containing the "IDE" (Ile-67, Asp-70, and Glu-71) epitope which is, therefore, implicated in the susceptibility of DR4' individuals to PV (10)(11)(12). Although the same IDE epitope is found in the third hypervariable region of the most-common DRw6 DRBI allele, 6A (Fig.…”
mentioning
confidence: 95%
“…Analysis of PCRamplified DNA from a panel of DR4' PV patients and controls with a set of DRBJ SSO probes revealed that nearly all (>95%) DR4+ PV patients carried the Dw10 DRBI allele, while the frequency of the oligonucleotide-defined DwJO DRBE allele in the HLA-matched control group was 5% (U.S. controls) (9) and 60% (Israeli Jewish controls) (10). In addition, sequence and SSO analysis of the DQB allele carried by the DR4+ PV and control groups showed that 92% of both patients and controls contained the DQB3.2 allele (10).…”
mentioning
confidence: 99%
See 3 more Smart Citations